Roldan Muradian and Esteve Corbera:: “The Simplicity of PES is Very Alluring, but We Cannot Use Simple Solutions to Solve Complex Problems” - Eloy, Ludivine; Coudel, Emilie (Sustainability in Debate, 2013)
Although there is currently a boom of Payment of Ecosystem Services (PES) initiatives in Latin America, including Brazil, little evidence about their effects or implications has been generated so far. In this sense, the application of policies without evidence is dangerous, alerts Roldan Muradian, a senior researcher at Radboud University Nijmegen, The Netherlands. Esteve Corbera, a senior research fellow at the Universitat Autònoma de Barcelona, in his turn emphasizes the importance of visualizing in which ways the rules that accompany PES implementation may or may not undermine the livelihood strategies of participants and non-participants. Muradian and Corbera - both of whom have spent the past 10 years researching on PES - have been internationally recognized due to their innovative approach to the matter, which goes beyond the conventional economic approach. Frequently coauthoring scientific articles on PES, both researchers use an institutional economy and political economy approach to analyze the origins, impacts and games of power associated with the implementation of PES in developing countries. While Muradian tries to better characterize market instruments and incentives for conservation, Corbera seeks to identify innovative and more effective ways to improve the implementation of PES. Corbera and Muradian were invited by Ludivine Eloy and Emilie Coudel to give an email interview to Sustainability in Debate. The main excerpts of the interview follow below.